Emily - Bedard, Michael, 1949-; Cooney, Barbara, 1917-2000. (New York : Dell Dragonfly Books, 2002)
When a mother and child pay a visit to their reclusive neighbor Emily, who stays in her house writing poems, there is an exchange of special gifts.
3.5
K-3
K-3
Elem. School Library Collection
Notable/Best Books (A.L.A.)
School Library Journal
Keywords: Dickinson, Emily, -- 1830-1886 -- Juvenile fiction; Dickinson, Emily, -- 1830-1886 -- Fiction; Neighborliness -- Fiction; Dickinson, Emily, -- 1830-1886 -- Fiction; Neighborliness -- Fiction